The Influence of Knowledge, Behaviour, Family Support and Paramedics’ Role Towards Visual Acuity in After-Surgery Cataract Patients in General Hospitals in Kediri - Dyah Novi Wulansari; Byba Melda Suhita; Siti Farida (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Cataract remains the major cause of blindness in the world, it also has important role in visual disturbance both in developed countries and developing countries. There are factors contributing in the improvement of visual acuity or the result of cataract surgery, some of which are after-surgery care, family’s ability to take care of the after-surgery patient, patient’s knowledge, patient’s behaviour, other underlying disease, and after-surgery complications. The purpose of this research was to seek the most influencing factor towards after-surgery visual acuity. This research was a quantitative research model with analytical observational method, using cross sectional approach. There were 63 respondents consist of cataract patients who has done surgery in general hospitals in Kediri, chose by simple random sampling method. Data analysing technique was done by double linier statistic test. The result of this research using double linier regression test with 63 respondents gave significant value of 0.000. This value was smaller than the p value (0.05 or 5%). This research analysis gave result in conclusion that there were significant effects of knowledge, respondents’ behaviour, family support, and paramedics’ role toward visual acuity in after-surgery cataract patients